Hysteresis and Lung Recruitment in Acute Respiratory Distress Syndrome Patients: A CT Scan Study*. Issue 10 (October 2020) - Chiumello, Davide; Arnal, Jean-Michel; Umbrello, Michele; Cammaroto, Antonio; Formenti, Paolo; Mistraletti, Giovanni; Bolgiaghi, Luca; Gotti, Miriam; Novotni, Dominik; Reidt, Sascha; Froio, Sara; Coppola, Silvia
Abstract : Objectives: Hysteresis of the respiratory system pressure-volume curve is related to alveolar surface forces, lung stress relaxation, and tidal reexpansion/collapse. Hysteresis has been suggested as a means of assessing lung recruitment. The objective of this study was to determine the relationship between hysteresis, mechanical characteristics of the respiratory system, and lung recruitment assessed by a CT scan in mechanically ventilated acute respiratory distress syndrome patients. Design: Prospective observational study. Setting: General ICU of a university hospital. Patients: Twenty-five consecutive sedated and paralyzed patients with acute respiratory distress syndrome (age 64 ± 15 yr, body mass index 26 ± 6 kg/m 2, PaO2 /FIO2 147 ± 42, and positive end-expiratory pressure 9.3 ± 1.4 cm H2 O) were enrolled. Interventions: A low-flow inflation and deflation pressure-volume curve (5–45 cm H2 O) and a sustained inflation recruitment maneuver (45 cm H2 O for 30 s) were performed. A lung CT scan was performed during breath-holding pressure at 5 cm H2 O and during the recruitment maneuver at 45 cm H2 O. Measurements and Main Results: Lung recruitment was computed as the difference in noninflated tissue and in gas volume measured at 5 and at 45 cm H2 O. Hysteresis was calculated as the ratio of the area enclosed by the pressure-volume curve and expressed as the hysteresis ratio. Hysteresis was correlated with respiratory system compliance computed at 5 cm H2 O and the lung gas volume entering the lung during inflation of the pressure-volume curve ( R 2 = 0.749, p < 0.001 and R 2 = 0.851, p < 0.001). The hysteresis ratio was related to both lung tissue and gas recruitment ( R 2 = 0.266, p = 0.008, R 2 = 0.357, p = 0.002, respectively). Receiver operating characteristic analysis showed that the optimal cutoff value to predict lung tissue recruitment for the hysteresis ratio was 28% (area under the receiver operating characteristic curve, 0.80; 95% CI, 0.62–0.98), with sensitivity and specificity of 0.75 and 0.77, respectively. Conclusions: Hysteresis of the respiratory system computed by low-flow pressure-volume curve is related to the anatomical lung characteristics and has an acceptable accuracy to predict lung recruitment. Abstract : Supplemental Digital Content is available in the text.